Cross-Cultural Awareness and Attitudes Toward Threatened Animal Species - Bruder, Jennifer; Burakowski, Lauren M.; Park, Taeyong; Al-Haddad, Reem; Al-Hemaidi, Sara; Al-Korbi, Amal; Al-Naimi, Almayasa (Frontiers in Psychology, 2022)
The preservation of our planet’s decreasing biodiversity is a global challenge. Human attitudes and preferences toward animals have profound impacts on conservation policies and decisions. To date, the vast majority of studies about human attitudes and concern toward animals have focused largely on western, educated, industrialized, rich and democratic (i.e., WEIRD) populations. In order to mitigate biodiversity loss globally, an understanding of how humans make decisions about animals from multicultural perspectives is needed. The present study examines familiarity, liking and endorsement of government protection amongst six broad cultural groups living in Qatar for five threatened animal species indigenous to the Arabian Gulf. Our findings highlight similarities and differences across cultures toward animals. Overall, familiarity did not predict endorsement for government protection after liking was accounted for. Liking, however, emerged as an important predictor of endorsement for government protection across cultures, although the degree of animal liking varied culturally. WEIRD and South East Asian participants showed similar and more positive attitudes toward animals compared to the other groups. Participants from the Arabian Gulf, Sub-Saharan Africa, Middle East and North Africa, and South Asia responded similarly toward the animals. Interestingly, the Arabian Gulf group demonstrated significantly less liking and protection endorsement for animals, including those animals which play an important role in their culture. This research highlights intriguing avenues for future research and points to liking as a possible universal human attitude toward animals that influences decision making about conservation across all cultures while suggesting applications for improving education.